2015
DOI: 10.1002/hep.27711
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in HFE C282Y homozygous men with extreme phenotypes identifies a GNPAT variant associated with severe iron overload

Abstract: To identify polymorphisms associated with variability of iron overload severity in HFE-associated hemochromatosis, we performed exome sequencing of DNA from 35 male HFE C282Y homozygotes with either markedly increased iron stores (n=22; cases) or with normal or mildly increased iron stores (n=13; controls). The 35 participants, residents of the U.S., Canada, and Australia, reported no or light alcohol consumption. Sequencing data included 82,068 single nucleotide variants, and 10,337 genes were tested for a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 47 publications
7
84
0
Order By: Relevance
“…McLaren et al (1) recently used whole-exome sequencing to show that GNPAT p.D519G (rs11558492) is associated with a high-iron phenotype in HFE C282Y homozygous men. Three other studies examined this association in different Caucasian populations with conflicting results.…”
Section: To the Editormentioning
confidence: 99%
“…McLaren et al (1) recently used whole-exome sequencing to show that GNPAT p.D519G (rs11558492) is associated with a high-iron phenotype in HFE C282Y homozygous men. Three other studies examined this association in different Caucasian populations with conflicting results.…”
Section: To the Editormentioning
confidence: 99%
“…A genome-wide association study (GWAS) identified the rs3811647 Tf polymorphism as the only SNP significantly associated with iron metabolism through serum transferrin and iron levels, indicating an indirect link with the phenotypic presentation of HFE-HH142 . More recently, in an exome sequencing study, a p.D519G variant in the glyceronephosphate Oacyltransferase (GNPAT) gene showed the most significant association with severe iron overload143 . Yet, this association has not been confirmed in a different hemochromatosis population144 .…”
mentioning
confidence: 99%
“…Archived sequence data may also become clinically relevant as sequence variants that affect disease severity (modifier genes) are identified, as evidenced by HFE dependent HH modifier gene, GNPAT. [14]…”
Section: Resultsmentioning
confidence: 99%